Adverse metabolic phenotype of adolescent girls with non-alcoholic fatty liver disease plus polycystic ovary syndrome compared with other girls and boys - Ayonrinde, Oyekoya; Adams, L.; Doherty, D.; Mori, T.; Beilin, L.; Oddy, W.; Hickey, M.; Sloboda, D.; Olynyk, John; Hart, R. (Wiley-Blackwell Publishing Asia, 2016)
Background and Aims: Non-alcoholic fatty liver disease (NAFLD) and polycystic ovary syndrome (PCOS) share risk associations of adiposity and insulin resistance. We examined the impact of a PCOS diagnosis on the metabolic phenotype of adolescent girls with NAFLD and compared this to girls without PCOS or NAFLD and to age-matched boys. Methods: Community-based adolescents from the Raine Cohort participated in assessments for NAFLD (572 girls and 592 boys) and PCOS (244 girls). One hundred and ninety-nine girls attended both assessments. Results: Amongst the 199 girls, PCOS was diagnosed in 16.1% and NAFLD in 18.6%. NAFLD was diagnosed in 10.1% of the boys. NAFLD was more prevalent in girls with PCOS than girls without PCOS (37.5% vs 15.1%, P = 0.003). Girls with NAFLD plus PCOS had greater adiposity (waist circumference, body mass index, suprailiac skinfold thickness [SST], serum androgens, high-sensitivity C-reactive protein, ferritin, homeostasis model assessment for insulin resistance (HOMA-IR), and lower serum sex hormone binding globulin levels than girls with NAFLD without a PCOS diagnosis (all P < 0.05).Girls with NAFLD plus PCOS had similar adiposity, HOMA-IR, and adiponectin levels to boys with NAFLD, but more adiposity, serum leptin and HOMA-IR than both girls and boys without NAFLD. PCOS (odds ratios 2.99, 95% confidence intervals 1.01–8.82, P = 0.048) and SST (odds ratios 1.14, 95% confidence intervals 1.08–1.20, P < 0.001) independently predicted NAFLD in adolescent girls, however, serum androgens and HOMA-IR levels did not. Conclusions: Adolescent girls with NAFLD plus PCOS have a similar metabolic phenotype to boys with NAFLD. Increasing SST and pre-existing PCOS independently predict NAFLD in adolescent girls.